A 'System of Self-Appointed Leaders'? Examining Modes of Muslim Representation in Governance in Britain. (May 2015) - Jones, Stephen H.; O'Toole, Therese; DeHanas, Daniel Nilsson; Modood, Tariq; Meer, Nasar
Research Highlights and Abstract This article Contributes to theoretical debates about the significance of group identity and political representation; Contributes to academic research into the shift from formal and hierarchical to more informal and network-based styles of governance; Contributes to research on the integration of Muslims in Britain by elucidating the emergence and diversification of Muslim representative organisations in Britain since 1970; Demonstrates the multifaceted and dynamic nature of Muslim representative claims-making in contemporary UK governance by identifying and analysing a range of modes of Muslim representation. Since the turn of the century Britain has seen a proliferation of Muslim civil society organisations and an increase in the number of points of contact between Muslim spokespersons and government. Yet, this increased participation in UK governance has been a source of fierce controversies centring on the role of conservative male leaderships and the influence of radical Islamic groups. Drawing on interviews with 42 national elites who have engaged in UK Muslim–government relations in the past decade, this article charts the emergence of national-level Muslim representation and assesses its relationship to democratic participation and accountability. Building on the work of Michael Saward, we argue that unelected civil society representatives can act as an important supplement to elected representatives. We show how four modes of Muslim representation have emerged in the last decade—'delegation', 'authority', 'expertise' and 'standing'—creating dynamic competition among representative claims.